MINORITY CONTRIBUTIONS TO THE HOSPITALITY INDUSTRY DURING THE AGE OF SEGREGATION - Hill, Brian (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
In the era of segregation, African Americans and other minority travelers often ran into institutionalized racism that legally prevented them from booking into and utilizing motels and hotels, restaurants and nightclubs, salons, and gas stations. The purpose of this review was to examine minority contributions to the hospitality industry during the age of segregation. I relied on a modified systematic review method and reviewed current literature on the phenomenon. Findings showed that it was mostly the African American community who opened their homes and hearts to these weary travelers, serving the African American community and other minorities in times of need.